Hypoxia is associated with a lower expression of genes involved in lipogenesis in visceral adipose tissue - García-Fuentes, Eduardo; Santiago-Fernández, Concepción; Gutiérrez-Repiso, Carolina; Mayas, María D.; Oliva-Olivera, Wilfredo; Coín-Aragüez, Leticia; Alcaide, Juan; Ocaña-Wilhelmi, Luis; Vendrell, Joan; Tinahones, Francisco J.; Garrido-Sánchez, Lourdes (Journal of translational medicine, 2015)
A key role for HIF-1α in the promotion and maintenance of dietary obesity has been proposed. We analyzed the association between hypoxia and de novo lipogenesis in human adipose tissue. We studied HIF-1α mRNA and protein expression in fasting status in visceral adipose tissue (VAT) from non-obese and morbidly obese subjects, and in VAT from wild-type and ob/ob C57BL6J mice in both fasting and feeding status. We also analyzed the effect of hypoxia on the VAT mRNA expression of genes involved in lipogenesis. HIF-1α was increased in VAT from morbidly obese subjects. In fasting status, C57BL6J ob/ob mice had a higher VAT HIF-1α mRNA expression than C57BL6J wild-type mice. In feeding status, VAT HIF-1α mRNA expression significantly increased in C57BL6J wild-type, but not in C57BL6J ob/ob mice. In humans, HIF-1α mRNA expression correlated positively with body mass index and insulin resistance. VAT HIF-1α mRNA expression correlated negatively with ACC1, PDHB and SIRT3 mRNA expression, and positively with PPAR-γ. VAT explants incubated in hypoxia showed reduced SIRT3 and increased PPAR-γ, SREBP-1c, ACLY, ACC1 and FASN mRNA expression. Morbidly obese subjects have a higher level of VAT HIF-1α. Postprandial status is associated with an increase in HIF-1α mRNA expression in C57BL6J wild-type mice. Hypoxia alters the mRNA expression of genes involved in de novo lipogenesis in human VAT.